اﻟﻌﻘﺎﺋد واﻟﻌﺑﺎدات ﻋﻧد اﻟﻌرب ﻗﺑل اﻻﺳﻼم (Journal of the College of Education for Women, 2019)
I explained in a few previous pages how the situation of the Arabs w ere before the mission of the p prophet Mohammed (the peace and blessing be upon him). The Arabs were illiteracy tribes in spite of some legislation which they had got from their father the prophet Ishmael (peace on him) there were some rules which were regulating their life during disputes. I mentioned the most important faiths which were adopted by the Arabs before Islam.Althaugh they believed in the existence of the one god, they worshiped idols. This type of the worshiped was inherited from other nations. Disputes and fighting covered and controlled their life for simple reasons. Disputes were responses for being as an important part of tribe community .Islam religion made great changes in their life after they believed in it .Islam re moved aII the corruptions from their community and strengthened charitable habits. In spite of good qualifications and moral habits the Arabs had before Islam ,but this were not leaded correctly to reform their community till the Islam came and changed everything correctly .and guide them towards unity and peace.